FBM, UiTM won three University Awards at Consultancy Annual Awards 2022 Ceremony - Bahrudin, Nur Zahidah (UiTM, 2023)
FBM, UiTM received three awards at the Consultancy Annual Awards 2022 Ceremony. The recognition highlights the faculty’s excellence in consultancy initiatives and its commitment to fostering impactful academic and professional contributions.